Analysis of the Theory of the Enactment of Islamic Law: Implications and Challenges in the Indonesian Context - Mappasessu, Mappasessu; Marilang, Marilang; Akmal, Andi Muhammad (Jurnal Hukum dan Keadilan, 2024)
Applying Islamic law, there needs to be a deep understanding of the theory of the enactment of Islamic law by the principles of national law, justice, and national values, this paper dissects the analysis of the theory of the enactment of Islamic law, How is the conceptual framework of the theory of the enactment of Islamic law in Indonesia, and What is the purpose of understanding the theory of the enactment of Islamic law in Indonesia, using the library research method is a study whose data is in the form of theories, concepts of thoughts and ideas, examining data and events that have occurred among Muslims in Indonesia in previous research, writing books and articles then continued research using relevant legal reasoning methodologies whose results found a condition that we can realize the complexity and challenges in integrating aspects of Islamic law into a country's national legal system,  including in the Indonesian context.